2001
DOI: 10.1093/jn/131.6.1700
|View full text |Cite
|
Sign up to set email alerts
|

High Linoleic Acid, Low Vegetable, and High Oleic Acid, High Vegetable Diets Affect Platelet Activation Similarly in Healthy Women and Men

Abstract: Upregulation of protein kinase C (PKC), an important enzyme in platelet activation, could be one step toward platelet hyperactivity. PKC activation can be modulated by dietary components in vitro, but few data are available concerning the in vivo effects. In this strictly controlled human dietary intervention, the influence of dietary unsaturated fatty acids and vegetable compounds on platelet activation was investigated. A high linoleic acid diet (10% of energy) with small amounts of vegetables (no berries or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…TXA2 has an important role in the progression of cardiovascular disease due to its acute and chronic effect in promoting platelet aggregation, vasoconstriction and cellular proliferation. However, differential effects of MUFA-rich diets with those rich in PUFA were not clear, suggesting controversial benefit effects on platelet activation comparing these type of oils [71].…”
Section: Evoo and Platelet Aggregationmentioning
confidence: 99%
“…TXA2 has an important role in the progression of cardiovascular disease due to its acute and chronic effect in promoting platelet aggregation, vasoconstriction and cellular proliferation. However, differential effects of MUFA-rich diets with those rich in PUFA were not clear, suggesting controversial benefit effects on platelet activation comparing these type of oils [71].…”
Section: Evoo and Platelet Aggregationmentioning
confidence: 99%
“…for intensive care patients. Several studies examined the influence of lipid emulsions at homeostasis [8,9,11,15] but, in this study, the influence of different lipid emulsions on platelet receptor expression was examined for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of lipid emulsions on platelet function and a modulation of coagulation is a controversial issue: some studies describe an impediment of the coagulation and platelet aggregation after consuming high-linoleic acid diets [7] or after an intravenous infusion of triglycerides [8]. Other studies had not found an influence of lipid emulsions containing n-3 fatty acid on coagulation and platelet function [9,10] or after a diet with high linoleic acid vs high oleic acid [11]. The structure of cell membranes seems to be modified by parenteral nutrition with lipid emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Misikangas et al found no differences in platelet aggregation or in protein kinase C (an important platelet regulator) induced by a diet high in linoleic acid but low in vegetables, as against one that was high in oleic acid and also vegetable-rich, although there is a certain complicating factor in interpreting this study due to the mixing of the potential effects of the fatty acids with those of the vegetables. Furthermore, the authors did not identify the origin of the oleic acid they employed [20].…”
Section: Platelet Aggregationmentioning
confidence: 99%